In pancreatic cancer, chemotherapy increases antitumor responses to tumor-associated antigens and potentiates DNA vaccination. Issue 2 (28th October 2020) - Mandili, Giorgia; Curcio, Claudia; Bulfamante, Sara; Follia, Laura; Ferrero, Giulio; Mazza, Emanuela; Principe, Moitza; Cordero, Francesca; Satolli, Maria Antonietta; Spadi, Rosella; Evangelista, Andrea; Giordano, Daniele; et al.
Abstract : Background: Pancreatic ductal adenocarcinoma (PDA) is an almost incurable tumor that is mostly resistant to chemotherapy (CT). Adaptive immune responses to tumor-associated antigens (TAA) have been reported, but immunotherapy (IT) clinical trials have not yet achieved any significant increase in survival, confirming the suppressive environment of PDA. As CT has immune-modulating properties, we investigated the effect of gemcitabine (GEM) in antitumor effector responses to TAA in patients with PDA. Methods: The IgG antibody repertoire in patients with PDA before and after CT was profiled by serological proteome analysis and ELISA and their ability to activate complement-dependent cytotoxicity (CDC) was measured. Peripheral T cells were stimulated in vitro with recombinant TAA, and specific proliferation, IFN-γ/IL-10 and CD8 + /Treg ratios were measured. Mice that spontaneously developed PDA were treated with GEM and inoculated with an ENO1 (α−Enolase) DNA vaccine. In some experimental groups, the effect of depleting CD4, CD8 and B cells by specific antibodies was also evaluated. Results: CT increased the number of TAA recognized by IgG and their ability to activate CDC. Evaluation of the IFN-γ/IL-10 ratio and CD8+/Treg ratios revealed that CT treatment shifted T cell responses to ENO1, G3P (glyceraldheyde-3-phosphate dehydrogenase), K2C8 (keratin, type II cytoskeletal 8) and FUBP1 (far upstream binding protein 1), four of the most recognized TAA, from regulatory to effector. In PDA mice models, treatment with GEM prior to ENO1 DNA vaccination unleashed CD4 antitumor activity and strongly impaired tumor progression compared with mice that were vaccinated or GEM-treated alone. Conclusions: Overall, these data indicate that, in PDA, CT enhances immune responses to TAA and renders them suitable targets for IT.